Binary Polyazides of Cerium and Gadolinium. Issue 6 (5th February 2018) - Rosenstengel, Kati; Schulz, Axel; Niehaus, Oliver; Janka, Oliver; Pöttgen, Rainer; Villinger, Alexander
Abstract : Herein, we report on the preparation and full characterization (melting point, ATR‐IR/Raman, elemental analysis, 14 N NMR) of binary gadolinium(III) azide as DMSO solvate Gd(N3 )3 · 8 /3 DMSO (DMSO = dimethylsulfoxide), along with the partially hydroxide substituted species Gd4 (OH)2 (N3 )10 · n DMSO ( n = 8, 10). Moreover, the isolation and comprehensive characterization of hexaazido lanthanate(III) anions [Ln(N3 )6 ] 3– (Ln = Ce, Gd) in a series of [Ph4 P] + and [EtPh3 P] + salts is presented. Single‐crystal structures of all compounds were determined, and the magnetic susceptibility in solution (NMR, Evans Method), as well as in the solid state (VSM), was investigated. Abstract : Gadolinium(III) azide Gd(N3 )3 · 8 /3 DMSO, the mixed azide/hydroxide derivatives Gd4 (OH)2 (N3 )10 · n DMSO ( n = 8, 10), and a series of hexaazido lanthanate(III) salts [M]3 [Ln(N3 )6 ]· n MeCN [Ln = Ce, Gd. [M] + = (Ph4 P) + ( n = 2), (EtPh3 P) + ( n = 0)] were synthesized and comprehensively characterized. The magnetic susceptibilities in solution as well as in the solid state were investigated.